Relationship between Microfinance and Economic Empowerment of Women Entrepreneurs in Matara District, Sri Lanka - Jayampathi E.K; Kaushalya M.K.D (International Journal of Small and Medium Enterprises and Business Sustainability, 2018)
The contribution of women entrepreneurs is a crucial factor in economic development in any country. Sri Lanka is highly benefitted from women entrepreneurship at the social and economic development in both qualitative and quantitative approaches. Therefore, it is essential to empower women in businesses to gain more desirable benefits for the country. Microfinance plays a vital role for women entrepreneurship development in developing countries. The microfinance has been identified by many scholars as one of the major weapons in empowering women entrepreneurs. Although there is a huge debate on microfinance as a crucial factor in order to determine the economic empowerment of women entrepreneurs, the contribution of microfinance of Sri Lankan context is questionable. Accordingly, this study focused on identifying the relationship between microfinance and empowering women entrepreneurs in Matara district, Sri Lanka. Population of this study was women entrepreneurs in Matara district and the sample consisted with 100 of women entrepreneurs those registered and received microfinance facilities from the HNB Grameen Finance Limited, Matara. Using a systematic sampling technique sample of the study was selected. Both primary and secondary data used to collect data for the purpose of this study. A self structured questionnaire used to gather primary data and interviews and discussions are also undertaken to gather relevant primary data where necessary. Correlation and regression analytical techniques used to analyze data. This study concluded that there is a positive relationship between microfinance and economic empowerment of women entrepreneurs. The findings show that there is a positive relationship between microcredit andmicro savings and economic empowerment of women entrepreneurs. As well as, results shown that there is not a significant relationship between micro insurance and economic empowerment of women entrepreneurs. Finally, the study suggests introducing suitable microfinance schemes as a strategy for increasing women entrepreneurs’ financial capabilities while strengthening their financial literacy. Microfinance institutions should responsible to train or educate women entrepreneurs before granting loan facilities or any other related microfinance products. Moreover, it is suggested to have enough awareness on record keeping, building assets, managing risk and increasing savings to get most desirable benefits for women entrepreneurs in businesses.